Agent-based models of administrative corruption: an overview. (4th March 2022) - Elnawawy M., Shaymaa; Okasha, Ahmed E.; Hosny, Hazem A.
ABSTRACT: Administrative corruption is a pervasive phenomenon that persists around the world regardless of the level of the country's development. It has been approached by various modeling techniques evolving out of different backgrounds. The most recent technique used is agent-based modeling which possesses analytical tools that reflect the heterogeneity and complexity of societies. This facilitates understanding corruption as an emergent property of the society's complex adaptive system. It provides more realistic and representative models that could be used by policy makers to build sound anti-corruption strategies. Hence, an overview of agent-based models that tackle administrative corruption has been presented in this article. The review revealed that this type of modeling is still evolving and provides a fertile field for further research, especially in regard to discovering the interdisciplinary mechanisms for corruption evolution. The article also suggests investigating some corruption-related topics using agent-based models such as: the complexity of the individual's decision-making process about corruption based on socio-psychological behavioral factors, the role of social ties and norms in the corruption process, the effect of the introduction of whistleblowers to the administrative system and the effect of automating the administrative governmental procedures on corruption emergence and evolution.